1984
DOI: 10.1093/carcin/5.5.661
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DMBA-induced mammary cancer by the monoterpene d-limonene

Abstract: We investigated whether the addition of d-limonene to the diets of rats would modify the process of mammary tumor induction by 7,12-dimethylbenz[a]anthracene (DMBA). When diets containing 1000 or 10 000 p.p.m. d-limonene were fed to rats from one week before DMBA administration to the end of the experiment (27 weeks post DMBA treatment), a significant reduction in mammary carcinogenesis was observed at each level. The inhibition of carcinogenesis was mainly due to an increase in latency; however, major differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(69 citation statements)
references
References 0 publications
1
67
0
1
Order By: Relevance
“…29 Limonene, the simplest monoterpene ( Figure 1) is able to both prevent and treat rat mammary tumors, and to treat advanced stomach, lung and liver cancers in rats. [30][31][32][33][34][35] The monohydroxylated derivative of limonene, perillyl alcohol (POH) (Figure 1) is 5-10 times more effective than limonene at treating advanced carcinomas. 36 In tumor-bearing animals fed monoterpenes, tumor regression is associated with an increase in apoptotic cells and a decrease in cell proliferation within the tumor parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…29 Limonene, the simplest monoterpene ( Figure 1) is able to both prevent and treat rat mammary tumors, and to treat advanced stomach, lung and liver cancers in rats. [30][31][32][33][34][35] The monohydroxylated derivative of limonene, perillyl alcohol (POH) (Figure 1) is 5-10 times more effective than limonene at treating advanced carcinomas. 36 In tumor-bearing animals fed monoterpenes, tumor regression is associated with an increase in apoptotic cells and a decrease in cell proliferation within the tumor parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Limonene has significant chemopreventive and chemotherapeutic activity without toxicity in rodents (Elegbede et al, 1984(Elegbede et al, , 1986Elson et al, 1988;Maltzman et al, 1989;Wattenberg et al, 1989Wattenberg et al, , 1991. Most studies have been directed at the use of limonene in the prevention of carcinogen-induced cancer (Wattenberg et al, 1983;Elegbede et al, 1984).…”
mentioning
confidence: 99%
“…Limonene has significant chemopreventive and chemotherapeutic activity without toxicity in rodents (Elegbede et al, 1984(Elegbede et al, , 1986Elson et al, 1988;Maltzman et al, 1989;Wattenberg et al, 1989Wattenberg et al, , 1991. Most studies have been directed at the use of limonene in the prevention of carcinogen-induced cancer (Wattenberg et al, 1983;Elegbede et al, 1984). It has been shown that limonene inhibits rat mammary carcinomas induced by both the indirectly acting carcinogen DMBA (Elegbede et al, 1984) and the directly acting carcinogen NMU (Maltzman et al, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 In established rat mammary carcinomas, limonene produces complete regression in > 80% of the tumors. 6,7 Perillyl alcohol is five-fold more potent than limonene in producing regression in both early 8 and advanced mammary tumors, 9 and also has activity in vivo against cancers of the pancreas, 10 melanoma 11 and liver 12 and in vitro against neuroblastoma 13 and colon carcinoma. 14 The exact mechanism for the anticancer activity of monoterpenes has not been fully established.…”
Section: Introductionmentioning
confidence: 99%